Research progress and limitation analysis of RNA interference in Haemonchus contortus in China - Hou, Bin; Hai, Ying; Buyin, Buhe; Hasi, Surong (Frontiers in Veterinary Science, 2023)
Haemonchus contortus is widely distributed around the world, as a highly pathogenic and economically important parasitic nematode of small ruminants, the related omics studies are more cutting-edge. However, there are fewer research tools to analyze the subsequent gene function studies by omics, RNA interference technology can specifically knock out or turn off the expression of specific genes, so this technology has been widely used to explore gene function and disease treatment research. In the present study, we review the novel research progress of RNA interference in Haemonchus contortus in recent years, aiming to provide a reference for the screening of RNA interference in key genes growth and development, drug resistance gene screening, diagnostic markers and diagnostic drug targets of Haemonchus contortus.